Implementasi Overall Equipment Effectiveness ( OEE ) Dalam Penerapan Metode Total Productive Maintenance (TPM) di PT. FJT - Zaenal Arifin, ST., MT (Universitas Riau Kepulauan, 2020)
Industry Sector of Vertical transportation, especially in the factory of PT. FJT, manufacturing system improvement is one of the efforts to increase that must be done intensively so that the results can respond to market changes quickly. The company always tries to increase productivity, one of the ways that has been done is to implement preventive and corrective maintenance. But in reality, the results have not reached expectations. Research on the Numerical Controll Turret machine in this company found that the time allocated to do damage maintenance is a major problem, so most of the corrective action is focused on this problem. This study uses OEE measurements, analysis of the calculation of the Six Great Losses, and also a causal diagram to look for existing problems and to provide suggestions for improvement for those problems. The measurement result obtained by OEE is 72.02%, the biggest factor influencing the low effectiveness of Mesen NCT is the 37.77% engine breakdown, which is the biggest among the 6 causal factors. .